(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to analyze the contribution of body structure and physical potential to 10×50-meter front crawl swimming performance among South Sulawesi athletes. Swimming performance, particularly in repeated middle-distance efforts, is theoretically influenced by the interaction between anthropometric characteristics and biomotor capacities, which determine propulsion efficiency, drag reduction, and metabolic sustainability. A quantitative correlational design was employed involving 45 competitive swimmers selected through purposive sampling. Body structure variables were assessed using standardized anthropometric measurements, including height, limb length, and body mass indicators, while physical potential was evaluated through validated tests of muscular strength, power, speed, flexibility, and cardiorespiratory endurance. Performance was measured using a 10×50-meter front crawl protocol representing repeated sprint-endurance demands. Data were analyzed using Pearson correlation and multiple regression tests at a 95% confidence level (α = 0.05). The results demonstrated a significant simultaneous relationship between body structure and physical potential with swimming performance (R = 0.845; p < 0.05; F = 52.298), with a coefficient of determination (R²) of 0.714. This indicates that 71.4% of performance variance is explained by the combined contribution of morphological and physiological factors. Athletes with more favorable anthropometric profiles and higher physical capacity achieved faster and more consistent swimming times. These findings highlight the importance of integrating anthropometric assessment and biomotor development into evidence-based training programs to optimize middle-distance front crawl performance.